Recent progress on action and regulation of anorexigenic adipokine leptin - Nakagawa, Tadashi; Hosoi, Toru (Frontiers in Endocrinology, 2023)
Organismal energy balance is controlled by inter-tissue communication mediated by the nervous system and hormones, the disruption of which causes metabolic syndrome exemplified by diabetes and obesity. Fat-storing adipose tissue, especially those located in subcutaneous white adipose tissue, secretes leptin in a proportion of fat mass, inhibiting the accumulation of organismal fat by suppressing appetite and promoting energy expenditure. With a prevalence of obesity that exhibits hyperleptinemia, most of the investigation on leptin has been focused on how it works and how it does not, which is expected to be a clue for treating obesity. In contrast, how it is synthesized, transported, and excreted, all of which are relevant to the homeostasis of blood leptin concentration, are not much understood. Of note, acute leptin reduction after hyperleptinemia in the context of obesity exhibited a beneficial effect on obesity and insulin sensitivity, indicating that manipulation of circulating leptin level may provide a therapeutic strategy. Technological advances such as “omics” analysis combined with sophisticated gene-engineered mice studies in the past decade enabled a deeper understanding of leptin’s action in more detail. Here, we summarize the updated understanding of the action as well as regulation of leptin and point out the emerging direction of research on leptin.